Manfaat Daun Belimbing Wuluh Sebagai Terapi dalam Membantu Pengobatan Penyakit Kardiovaskular (Hipertensi) - Yelfi Anwar; Egy Octaviani; Grace Tandiseru; Laila Safa Asrianti; Rafael Rafael; Risty Setyati Ashari; Raden Roro Putri Nur Ramadhania (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2024)
Hypertension is one of the most common and serious health problems in society, which can cause complictions such as heart disease, stroke and kidney failure. This study examines the use of starfruit leaves (Averrhoa bilimbi) as an adjuvant therapy in the treatment of hypertension. The aim of this community service program is to increase public knowledge and understanding of the benefits of starfruit leaves in the treatment of hypertension, as well as provide education on how to process starfruit leaves into a safe and effective herbal concoction. The results of the pre-test and post-test obtained showed that the pre-test percentage was correct at 88.7% and the percentage value incorrect was 12.3%, while the post-test percentage correct was 98.7% and the percentage value incorrect was 2.3%. The conclusion of this program is that education regarding the use of starfruit leaves can increase public understanding about alternative treatments for hypertension based on local plants.